Nurses' knowledge and practices regarding pain management in newborns - Taine Costa; Lisabelle Mariano Rossato; Mariana Bueno; Izabela Linha Secco; Natália Pinheiro Braga Sposito; Denise Harrison; Júnia Selma de Freitas
Abstract OBJECTIVE To analyze nurses' knowledge and practices regarding pain management of newborns admitted to Neonatal Intensive Care Units. METHOD A descriptive and cross-sectional study. Data were collected from 51 nurses based on an adapted questionnaire aimed at evaluating knowledge and practices regarding the management of neonatal pain in six hospitals in Curitiba and its Metropolitan Region. RESULTS For most nurses (86.0%), neonates feel pain. A total of 34.7% of the nurses reported never using pain assessment scales. Pain management was recorded by 84.3% of the nurses. Administered pharmacological measures were Paracetamol and Fentanyl (47.1%) and Morphine (17.6%); while non-pharmacological measures adopted were sweetened solution (68.6%), non-nutritive sucking (58.8%) and positioning (56.9%). CONCLUSION Nurses considered neonatal pain a real event; however, they do not perform pain assessment or treatment of newborns in a systematized way.It is necessary to implement knowledge translation strategiesin order to improve pain management in newborns.